Implementation Of The Preisach Model In A Simulation Environment For Virtual Experiments With Magnetic Hysteresis - humam, muhammad adib; boediardjo, kirina wulandari; ströhla, tom (Liaison Journal of Engineering, 2021)
There is a few simulation environment to implement the Preisach model of magnetic hysteresis. In this simulation, the changes of magnetic field strength and magnetic flux density will be observed. Magnetic hysteresis are commonly used in ferromagnetic and ferrimagnetic material analysis. The relationship between magnetic field strength and magnetic flux density is then represented in a B-H curve. The idea is that the B-H curve will be analyzed using Preisach model. Then, the data that is obtained could be analyzed further. Keywords: Preisach Model